2017
DOI: 10.3389/fmicb.2017.00454
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis Reveals a Correlation between the Host Phylogeny, Gut Microbiota and Metabolite Profiles in Cyprinid Fishes

Abstract: Gut microbiota play key roles in host nutrition and metabolism. However, little is known about the relationship between host genetics, gut microbiota and metabolic profiles. Here, we used high-throughput sequencing and gas chromatography/mass spectrometry approaches to characterize the microbiota composition and the metabolite profiles in the gut of five cyprinid fish species with three different feeding habits raised under identical husbandry conditions. Our results showed that host species and feeding habits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 75 publications
4
53
0
Order By: Relevance
“…Third, the presence of similar bacterial taxa in the gut microbiota of multiple fish species suggests that these bacteria are valuable for the host and could play important roles in digestion, nutrient absorption and immune response 8 . Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria have been found in the intestines of many marine and freshwater fish species 9,10,[28][29][30] and other Cyprinidae species 31 . Moreover, a number of studies of fish have found that these phyla are present in proportions similar to those in our study 24,32,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the presence of similar bacterial taxa in the gut microbiota of multiple fish species suggests that these bacteria are valuable for the host and could play important roles in digestion, nutrient absorption and immune response 8 . Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria have been found in the intestines of many marine and freshwater fish species 9,10,[28][29][30] and other Cyprinidae species 31 . Moreover, a number of studies of fish have found that these phyla are present in proportions similar to those in our study 24,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…(2020) 10:4460 | https://doi.org/10.1038/s41598-020-61351-1 www.nature.com/scientificreports www.nature.com/scientificreports/ their percent abundance was lower, Clostridium and Bacteroidetes were also present in all examined groups; these taxa have also been found in other herbivorous carps . It is interesting to note that all these bacteria are widely known as cellulose-degrading bacteria, which are particularly important for food degradation in the gut of herbivores 31 . Thus, these findings suggest that these bacteria co-create the main stem of the Cyprinidae microbiome and are necessary to break down nutrients in digestive-tract contents.…”
Section: Discussionmentioning
confidence: 99%
“…The enriched bacteria at genus level in the probiotic fed marron can be correlated with better growth and immune performance and water quality from previous studies. For instances, Pirellula abundance was found correlated to essential amino acids such as isoleucine, leucine and valine production in grass carp (Ctenopharyngodon idellus) and blunt snout bream (Megalobrama amblycephala) 34 . Another genus Reyranella that is phylogenetically very close to Rhodospirillaceae, also reported to play a crucial role in nitrate reduction from soil and freshwater 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…DNA was isolated and purified using an E.Z.N.A. ® Stool DNA Kit (Omega Bio-tek, Norcross, GA, U.S.) according to the manufacturer's protocols 56 . The DNA quality and concentration were checked on a 1.0% agarose gel after electrophoresis and a NanoDrop ND-2000 spectrophotometer (Thermo Fisher Scientific, United States), respectively.…”
Section: Dna Extraction and Pcr Amplificationmentioning
confidence: 99%